Spirit of the Delta : the art of Carolyn Norris - Shawhan, Dorothy (University Press of Mississippi, 2011)
Carolyn Norris: a life in color -- Carolyn Norris : "a moment that i felt something" / Patti Carr Black -- Interview with Carolyn Norris / by Tom Rankin.